Adaptive regulation of digestive serine proteases in the larval midgut of Helicoverpa armigera in response to a plant protease inhibitor. (April 2015) - Kuwar, Suyog S.; Pauchet, Yannick; Vogel, Heiko; Heckel, David G.
Abstract: Protease inhibitors (PIs) are direct defenses induced by plants in response to herbivory. PIs reduce herbivore digestive efficiency by inhibiting insects' digestive proteases; in turn insects can adapt to PIs by generally increasing protease levels and/or by inducing the expression of PI-insensitive proteases. Helicoverpa armigera, a highly polyphagous lepidopteran insect pest, is known for its ability to adapt to PIs. To advance our molecular and functional understanding of the regulation of digestive proteases, we performed a comprehensive gene expression experiment of H . armigera exposed to soybean Kunitz trypsin inhibitor (SKTI) using a custom-designed microarray. We observed poor larval growth on the SKTI diet until 24 h, however after 48 h larvae attained comparable weight to that of control diet. Although initially the expression of several trypsins and chymotrypsins increased, eventually the expression of some trypsins decreased, while the number of chymotrypsins and their expression increased in response to SKTI. Some of the diverged serine proteases were also differentially expressed. The expression of serine proteases observed using microarrays were further validated by qRT-PCR at different time points (12, 24, 48, 72 and 96 h) after the start of SKTI ingestion. There were also large changes in transcriptional patterns over time in the control diet. Carbohydrate metabolism and immune defense genes were affected in response to SKTI ingestion. Enzyme assays revealed reduced trypsin-specific activity and increased chymotrypsin-specific activity in response to SKTI. The differential regulation of trypsins and chymotrypsins at the transcript and protein levels accompanying a rebound in growth rate indicates that induction of SKTI-insensitive proteases is an effective strategy of H . armigera in coping with this protease inhibitor in its diet. Graphical abstract: Highlights: Soybean Kunitz trypsin inhibitor temporarily slows growth of cotton bollworm larvae. Microarrays revealed enhanced or suppressed expression of proteases and other genes. Enzyme assays revealed an increase in inhibitor-insensitive chymotrypsins.